2019
DOI: 10.1093/nsr/nwz110
|View full text |Cite
|
Sign up to set email alerts
|

Log-periodic quantum magneto-oscillations and discrete-scale invariance in topological material HfTe5

Abstract: Discrete scale invariance (DSI) is a phenomenon featuring intriguing log-periodicity which can be rarely observed in quantum systems. Here we report the log-periodic quantum oscillations in the magnetoresistance (MR) and the Hall traces of HfTe 5 crystals, which reveals the appearance of DSI. The oscillations show the same logB-periodicity in the behavior of MR and Hall, indicating an overall effect of the DSI on the transport properties. Moreover, the DSI feature in the Hall resistance signals its close relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Log-Periodic MR/Hall Oscillations. Unusual properties of material systems under the quantum limit, wherein all of the carriers are condensed to the lowest Landau level, have been a topic of interest since their discovery (21,22,(39)(40)(41)(42)(43)(44). As a promising candidate for "Weyl semiconductor" with a relatively small carrier density and unique band topology, Te offers a suitable platform for the study of Weyl physics beyond the quantum limit.…”
Section: Phementioning
confidence: 99%
See 2 more Smart Citations
“…Log-Periodic MR/Hall Oscillations. Unusual properties of material systems under the quantum limit, wherein all of the carriers are condensed to the lowest Landau level, have been a topic of interest since their discovery (21,22,(39)(40)(41)(42)(43)(44). As a promising candidate for "Weyl semiconductor" with a relatively small carrier density and unique band topology, Te offers a suitable platform for the study of Weyl physics beyond the quantum limit.…”
Section: Phementioning
confidence: 99%
“…4A shows the MR data taken under static fields at 1.8 K, which exhibit oscillations with more periods. Following previous studies (21,22), a suitable background (SI Appendix, Fig. S15A) obtained via smoothing was subtracted to better distinguish the oscillations (Materials and Methods).…”
Section: Phementioning
confidence: 99%
See 1 more Smart Citation
“…In the quantum limit, our theory have shown that up to two resistance dips may appear if the system is a 3D strong topological insulator [12]. Surprisingly, recent experiments report up to five oscillations in the quantum limit [258,259]. The oscillation as a function of the magnetic field follows a logithimic scale invariance law, much like those in the Efimov bound states of cold atoms.…”
Section: Remarks and Perspectivementioning
confidence: 70%
“…Efimovlike bound states have been used to understand the unexpected oscillations [260,261]. A direct fitting of the resistance in the experiment have also been demonstrated [258,259,261]. Nevertheless, other mechanisms that may lead to the scale invariance oscillations will be topics of broad interest.…”
Section: Remarks and Perspectivementioning
confidence: 99%